Moore's law, Dabbawalas, and pediatric cardiac care in Sri Lanka - Duminda Samarasinghe (Wolters Kluwer Medknow Publications, 2015)
Sri Lanka is an island nation in Indian Ocean that provides free healthcare to all citizens through government healthcare system. It has commendable health indices in the region. Pediatric cardiac services have rapidly progressed over past few years helping to further bring down infant and under-five mortality rates. Lady Ridgeway Hospital for Children (LRH) is the only tertiary care referral center for children with heart disease in the country. Currently it performs approximately 1,000 cardiac catheterizations and 1,000 cardiac surgeries every year. Target is to double the surgical output to treat all children with heart diseases in a timely and appropriate manner. Being a middle-income country, this is not an easy task. Technology used in diagnosis and treatment of congenital heart diseases is rapidly advancing with its price tag. In such a setting, it is challenging to proceed to achieve this target in a resource-limited environment.